2016
DOI: 10.1039/c6ra18360c
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the silanization of thermally-decomposed iron oxide nanoparticles for efficient aqueous phase transfer and MRI applications

Abstract: A facile silanization method allows to efficiently stabilise in aqueous solution iron oxide NPs synthesized by thermal decomposition for MRI applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
4
9
1
Order By: Relevance
“…In a previous study on the same kind of IO NPs coated with TPEDTA siloxane (free silica) instead of MS-HSA shell, we obtained a r1 of 13.9 mM -1 s -1 and a r2 of 88.6 mM -1 s -1 . [32] Our present study here on IO@MS-HSA NPs showed that the MS-HSA coating on the IO NPs did not modify importantly the r2 value as compared to IO@TPEDTA but strongly decreased the r1 leading to a higher r2/r1 ratio. This low r1 value could be explained by a limited water accessibility to the magnetic core due to the MS-HSA coating.…”
Section: Evaluation Of Mri Contrast Properties Of Io@ms-hsacontrasting
confidence: 44%
“…In a previous study on the same kind of IO NPs coated with TPEDTA siloxane (free silica) instead of MS-HSA shell, we obtained a r1 of 13.9 mM -1 s -1 and a r2 of 88.6 mM -1 s -1 . [32] Our present study here on IO@MS-HSA NPs showed that the MS-HSA coating on the IO NPs did not modify importantly the r2 value as compared to IO@TPEDTA but strongly decreased the r1 leading to a higher r2/r1 ratio. This low r1 value could be explained by a limited water accessibility to the magnetic core due to the MS-HSA coating.…”
Section: Evaluation Of Mri Contrast Properties Of Io@ms-hsacontrasting
confidence: 44%
“…4. 37,38 The peak near 686 cm À1 corresponds to both the Fe-O bond stretching of iron oxide and the amide V (a and b) of the pristine PA6. 39 However, interaction between the peaks results in the suppression of the peak near 686 cm À1 for the 22 wt.% and 55 wt.% PNCs.…”
Section: Fourier-transform Infrared Spectroscopymentioning
confidence: 99%
“…The loading/release upon thermal response can be done using "grafting-to" and "grafting-from" methods. Graftingto strategies involve the functionalization of IONPs by polymers either by non-covalent interactions [88,116] or by strong interactions (coordination/electro-covalent) using anchoring groups such as phosphonate [72,117,118], carboxylate [119] or alkoxysilane [120][121][122][123]. In these different cases of chemisorption, multivalency is an important way to increase the binding strength e.g.…”
Section: Formulation Of Drugs and Magnetic Nps In Thermally Sensitivementioning
confidence: 99%